Exclusive focus particles and their syntax & scope-taking in English, Vietnamese, and Korean - Park, Myung-Kwan (Linguistic research, 2020)
This paper concentrates on the syntax and scope-taking of the exclusive focus particles in English, Vietnamese, and Korean. We first note that unlike in English, in Vietnamese the focus particle 'chi' cannot occur on VP-internal elements. Building on this dichotomy between the two languages, we develop and endorse a movement analysis of focus particles. Specifically, we argue that Vietnamese 'chi' and English 'only' at VP-peripheral position are moved overtly from VP-internal position to the Spec of the null Sigma head, thereby serving as a scope marker at its landing site. When at pre-subject position, however, they are not granted a licensing Sigma head in the upper TP domain, thus embracing the in-situ strategy for scope-taking. Meanwhile, unlike its Vietnamese counterpart, English 'only' overtly staying in VP-internal position undergoes covert movement to take propositional scope. Now in a parallel fashion to English 'only' at VP-internal position, the Korean focus particle '-man' unmarkedly undergoes not overt but covert movement to the Spec of the null Sigma head, which also in turn counts as a scope marker. At the same time, it can markedly take the overt movement strategy, landing at the right periphery of VP.